2017
DOI: 10.1016/j.shaw.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Status of Laboratory Biosafety and Biosecurity in Veterinary Research Facilities in Nigeria

Abstract: BackgroundThis study determined current status of laboratory biosafety in Nigerian veterinary research facilities.MethodsA questionnaire was developed to obtain information from researchers across Nigeria from July 2014 to July 2015. Information regarding demographics, knowledge of laboratory biosafety, availability and proper use of personal protective equipment (PPE), any priority pathogens researched, attitude on and use of standard laboratory practices, and biosafety awareness was obtained using a numeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…A dependent variable was created from the thematic questions below, which were used to determine the knowledge levels of Nigerian undergraduate DVM students on antibiotic use and AMR; related questions (variables) were categorized together into various outcomes: (1) Antimicrobial resistance in humans; (2) antimicrobial resistance in animals; (3) contributory factors to antimicrobial resistance; and (4) overall knowledge on antimicrobial resistance. A numeric scoring system was used [32] to assess these outcome variables: To compute these outcome variables, respondents' responses to questions asked were scored as "correct" or "incorrect" and transformed as "1" or "0", respectively. The correct responses to questions in each category were added to give the general knowledge score for each of the outcome variables.…”
Section: Data Management and Analysismentioning
confidence: 99%
“…A dependent variable was created from the thematic questions below, which were used to determine the knowledge levels of Nigerian undergraduate DVM students on antibiotic use and AMR; related questions (variables) were categorized together into various outcomes: (1) Antimicrobial resistance in humans; (2) antimicrobial resistance in animals; (3) contributory factors to antimicrobial resistance; and (4) overall knowledge on antimicrobial resistance. A numeric scoring system was used [32] to assess these outcome variables: To compute these outcome variables, respondents' responses to questions asked were scored as "correct" or "incorrect" and transformed as "1" or "0", respectively. The correct responses to questions in each category were added to give the general knowledge score for each of the outcome variables.…”
Section: Data Management and Analysismentioning
confidence: 99%
“…3 An earlier study conducted in Nigeria raised concern about the levels of negligence in laboratory biosafety and biosecurity at VL facilities in the country. 6 Laboratories visited in this study lack BSL facilities and functional BSCs. The majority of the laboratories provide teaching, research, diagnostic, and healthcare services (public health, clinical, or hospital based) and supposedly should be designed as BSL-2 or above.…”
Section: Discussionmentioning
confidence: 99%
“…5 Recently, emerging and reemerging infectious and zoonotic diseases are increasing threats, particularly in Africa, including those with bioterrorism potential. 6,7 Concerns surrounding the deliberate or accidental release of potentially pathogenic microorganisms have driven the debate regarding the restriction of access to high-consequence pathogens and improving biosecurity measures, especially for those pathogens that have the potential to spread rapidly in the community. 8 As emerging and recurring global health threats expand their frontiers, in the short and longer terms, sustainable strategic approaches are needed to mitigate their impacts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, intrinsic knowledge and educational efforts can contribute to a general culture of laboratory biosafety. Odetokun et al (31) reported that 5.4% of participants in a survey of Nigeria veterinary laboratories demonstrated a satisfactory knowledge of laboratory biosafety and security, while 94.6% demonstrated poor knowledge. Among the researchers, 25.7% and 74.3% were documented to have high and low levels of awareness about biosafety, respectively.…”
Section: Discussionmentioning
confidence: 99%